China’s City size distribution: diverging in terms of people and converging in terms of urbanized area - Zhang, Xiaoxuan; Li, Chao; Gibson, John (Letters in spatial and resource sciences, 2025)
The changing size distribution of cities in China affects productivity, food security, resource use, and macroeconomic fragility. The legacy of central planning, and especially the mobility restrictions from hukou registration, hampered evolution of the city size distribution, creating a need for rapid adjustment in city sizes in the more market-oriented era. We use China’s three latest censuses of population (for 2000, 2010 and 2020) to show how the city size distribution is changing, for 265 cities containing 98% of China’s urban residents. We also form remote sensing estimates of urbanized area for the same cities and same period. Rank-size regressions show that the population distribution of cities is becoming less equal over time, while urbanized area is becoming more equal. The population growth of many big cities is not being aided by fast enough urban area expansion in those places, but urban area elsewhere expands faster than required by slow growth in their number of residents. The elasticity of changes in population density with respect to changes in city population exceeds 0.5 for cities in China’s eastern region but is significantly lower in the central region and lower still in the western region, where growth in city population is almost entirely accommodated by growth in city area, with little change in density. We relate these diverging trends to China’s macroeconomic fragility coming from the real estate sector and to regional differences in urban agglomeration effects that may generate productive spillovers.